Exploring the gut microbiota of rural region of Haryana (India): sociodemographic, socioeconomic factors and lifestyle - Suchandra Gupta; Manisha Khandait; Sandhya Khunger (Elsevier, 2024)
Background: The normal gut microbiota serves numerous functions in our body, which includes metabolism of food and drugs, maintenance of integrity of mucosal barrier and also protection against pathogens. Various factors are responsible in designing the structure of gut microbiota such as diet, lifestyle, sociodemographic and socioeconomic factors. The aim of the research was to study the composition of gut microbiota of individuals from rural regions of Haryana and to understand the impact of sociodemographic factors, lifestyle, and socioeconomic status on the diversity of gut microbiota. Methods: A cross-sectional study was conducted on 200 healthy individuals from rural region of Haryana, data pertaining to their socioeconomic and sociodemographic factors, lifestyle and diet was recorded through a questionnaire, followed by the processing of stool samples by both culture-dependent and independent techniques. Results: Out of the 200 samples, the abundance of phylum Firmicutes, Bacteroidetes, Actinobacteria, and Proteobacteria were found. High alpha diversity with less beta diversity was observed. High counts of Lactobacillus, Bifidobacterium and Prevotella were found among males, whereas among females high abundance of Fusobacterium, Streptococcus, Enterococcus and E.coli were found. Occupation wise we found increased abundance of Bifidobacterium, Clostridium, Bacteroides, Rhuminicoccus and Salmonella in homemakers, whereas among employed subjects abundance of Lactobacillus and Yersinia were increased. Presence of butyrate producing bacteria (Bifidobacterium and Lactobacillus) among the subjects with sufficient sleep was also recorded. Conclusion: While comparing the association of gut microbiota with various sociodemographic factors, we found differences in the phylum abundance, but statistically it was nonsignificant. Whereas positive association was observed between gut microbiota and healthy lifestyle which includes consumption of balanced diet, non smokers, sufficient water intake and good quality of sleep.